Macular Ganglion Cell and Retinal Nerve Fiber Layer Thickness in Children With Refractive Errors—An Optical Coherence Tomography Study. Issue 7 (July 2017) - Goh, Jody P.; Koh, Victor; Chan, Yiong Huak; Ngo, Cheryl
Abstract : Purpose: To study the distribution of macular ganglion cell-inner plexiform layer (GC-IPL) thickness and peripapillary retinal nerve fiber layer (RNFL) thickness in children with refractive errors. Materials and Methods: Two hundred forty-three healthy eyes from 139 children with refractive error ranging from −10.00 to +5.00 D were recruited from the National University Hospital Eye Surgery outpatient clinic. After a comprehensive ocular examination, refraction, and axial length (AL) measurement (IOLMaster), macular GC-IPL and RNFL thickness values were obtained with a spectral domain Cirrus high definition optical coherence tomography system (Carl Zeiss Meditec Inc.). Only scans with signal strength of >6/10 were included. Correlation between variables was calculated using the Pearson correlation coefficient. A multivariate analysis using mixed models was done to adjust for confounders. Results: The mean spherical equivalent refraction was −3.20±3.51 D and mean AL was 24.39±1.72 mm. Average, minimum, superior, and inferior GC-IPL were 82.59±6.29, 77.17±9.65, 83.68±6.96, and 81.64±6.70 μm, respectively. Average, superior, and inferior peripapillary RNFL were 99.00±11.45, 123.20±25.81, and 124.24±22.23 μm, respectively. Average, superior, and inferior GC-IPL were correlated with AL (β=−2.056, P -value 0.000; β=−2.383, P -value 0.000; β=−1.721, P -value 0.000), but minimum GC-IPL was not (β=−1.056, P -value 0.115). None of the RNFL parameters were correlated with AL. Conclusions: This study establishes normative macular GC-IPL and RNFL thickness in children with refractive errors. Our results suggest that high definition optical coherence tomography RNFL parameters and minimum GC-IPL are not affected by AL or myopia in children, and therefore warrants further evaluation in pediatric glaucoma patients.